A well-timed shift from local to global agreements accelerates climate change mitigation - Vadim A. Karatayev (Nature Portfolio, 2021)
Do we mitigate climate change in a Kyoto style global agreement or via multiple agreements among smaller groups of states? Here the authors show that the best strategy may begin with regional legally binding, aggressive agreements and, as these become common, renew pursuit of a global legally-binding treaty.